(untitled) (Cardiovascular Journal, 2011)
Background: Now a days mitral balloon valvoplasty(PTMC) is an alternative to closed surgical mitral commissurotomy (CMC) for the treatment of selectcd patients with rheumatic mitral stenosis. To compare between the total echo score (Wilkin’s score) total echocardiographic commissural morphology score (TC) for outcome and as a predictors of complications of both procedures. Method: We carried out a prospective well matched comparative observational study on 123 patients of symptomatic mitral and three patients were rejected due to procedural complications and technical failure. Result: Age ranges were 12 55 years, mean (±SD) age was 28.83+9.33 years. Out of 120 patients, 41 (34.2%) were male and 79 (65.8%) were female. Before procedure, 29 (48.3 %) and 32 (53.3 %) patients were in NYHA class III.Total Wilkins score was in the range of 4 10. Mean (±SD) of total Wilkins score were 6.43+1.53 and 6.30+1.33. Good commissural morphology (score 0 1) were present in 38 (63.5%) and 36 (60%) and bad commissural morphology (score 2 3) were present in 22 (26.7 %) and. 24 (40 %) in both groups respectively. Mitral valve area increased from a mean (±SD) of 0.80±0.16 and 0.79±0.15 to 1.94 ±0.24 and 1.92 + 0.26cm2. in PTMC and CMC groups respectively. Transmitral mean and peak pressure gradient also decreased significantly in both the individual procedures but no statistically significant difference between the procedures. NYHA class improved by class 1 or more in most patients in both groups. There were 2 (3.33 %) cases of cardiac temponade due cardiac perforation in PTMC group, of which one need repair and CMC and another was managed conservatively. There were also 3 (5 %) patients in PTMC and I (1. 66 %) patient in CMC developed peripheral thromboembolism and one patient (1.66%) developed arteriovenous fistula in PTMC group. Mitral regurgitation grade III, developed in 3 (5%) patients and one patient (1.66%) in PTMC and CMC respectively having no statistical significance. Conclusion: Total Wilkin’s score and total commissural morphology score were found to be most important preprocedural variable associcated with the outcome and as a predictors of post procedural complications Keywords: PTMC, CMC, Mitral stenosis, Rheumatic heart disease DOI: http://dx.doi.org/10.3329/cardio.v1i1.8202 Cardiovasc. j. 2008; 1(1) : 34-43